Selected Areas in Cryptography 16th International Workshop, SAC 2009, Calgary, Alberta, Canada, August 13-14, 2009, Revised Selected Papers - Jacobson, Michael J.; Rijmen, Vincent; Safavi-Naini, Rei (Security and Cryptology, 2009)
This volume constitutes the selected papers of the 16th Annual International Workshop on Selected Areas in Cryptography, SAC 2009, held in Calgary, Alberta, Canada, in August 13-14 2009. From a total of 99 technical papers, 27 papers were accepted for presentation at the workshop. They cover the following topics: hash functions, on block and stream ciphers, public key schemes, implementation, and privacy-enhancing cryptographic systems.